Influence of Emojis on Online Trust Among College Students - Zhang, Mei; Ding, Shuheng; Liu, Yining; Li, Hailong; Zhu, Yanchun; Qin, Chunlei (Frontiers in Psychology, 2021)
The use of emojis continues to grow, especially among college students. That said, little research has been performed examining the relationship between emojis and online trust. Three experimental studies were carried out to assess the impact of the use of different emojis on online trust. In the first experiment, 62 college students were recruited as subjects. The results indicated that the initial online trust of our smiling face group was significantly higher than that of the control group. To further investigate the relationship between other emojis and initial online trust, 74 college students participated in the second experiment; no significant difference in initial online trust was found between our sad face group and the control group. Joint data analysis showed that the initial online trust level of the smiling face group was significantly higher than that of the sad and control groups; however, the difference between the latter two groups was not significant. Further research was conducted to explore the influence of emojis on online trust among acquaintances. The third experiment (111 college student participants) found that an individual’s capacity for trust played a moderating role when it came to the relationship between emojis and acquaintances. That is, when an individual’s tendency to trust was low, the online trust level of the smiling face group was significantly higher than that of the sad group. That said, there was no difference between the smiling face group and the control group. Moreover, there were no significant differences among the three groups when an individual’s tendency to trust was high. The results show that emotional information conveyed by emojis significantly affects the initial online trust of strangers on the internet, but it only affects the interpersonal online trust of acquaintances when an individual’s tendency to trust is already low.